Long‐term clinical, virological and immunological outcomes following planned treatment interruption in HIV‐infected children. Issue 3 (29th October 2020) - Freguja, R; Bamford, A; Zanchetta, M; Del Bianco, P; Giaquinto, C; Harper, L; Dalzini, A; Cressey, TR; Compagnucci, A; Saidi, Y; Riault, Y; Ford, D; et al.
Abstract : Objectives: Planned treatment interruption (PTI) of antiretroviral therapy (ART) in adults is associated with adverse outcomes. The PENTA 11 trial randomized HIV‐infected children to continuous ART (CT) vs . CD4‐driven PTIs. We report 5 years' follow‐up after the end of main trial. Methods: Post‐trial, all children resumed ART. Clinical, immunological, virological and treatment data were collected annually. A sub‐study investigated more detailed immunophenotype. CT and PTI arms were compared using intention‐to‐treat. Laboratory parameters were compared using linear regression, adjusting for baseline values; mixed models were used to include all data over time. Results: In all, 101 children (51 CT, 50 PTI) contributed a median of 7.6 years, including 5.1 years of post‐trial follow‐up. Post‐trial, there were no deaths, one pulmonary tuberculosis and no other CDC stage B/C events. At 5 years post‐trial, 90% of children in the CT vs . 82% in the PTI arm had HIV RNA < 50 copies/mL ( P  = 0.26). A persistent increase in CD8 cells was observed in the PTI arm. The sub‐study (54 children) suggested that both naïve and memory populations contributed to higher CD8 cells following PTI. Mean CD4/CD8 ratios at 5 years post‐trial were 1.22 and 1.08 in CT and PTI arms, respectively [difference (CT – PTI) = −0.15; 95% CI: −0.34–0.05), P  = 0.14]. The sub‐study also suggested that during the trial and at early timepoints after the end of the trial, reduction in CD4 in the PTI arm was mainly from loss of CD4 memory cells. Conclusions: Children tolerated PTI with few long‐term clinical, virological or immunological consequences.